Letter to AAOAJ: Dark Matter May Not Exist (Global Journal of Science Frontier Research, 2018)
Twenty-First Century Theoretical Physics may be in a state akin to 19th century Physics prior to Einstein's Relativity Paradigmatic Shift and Quantum Mechanics discovery; This is because the two primary pillars of Modern Physics, namely RT and QM seem inconsistent (e.g., such as the apparent contradiction that exists between QM's "quantum entanglement" phenomenon indicating the possibility of "non-local" instantaneous effects as opposed to RT's strict constraint imposed upon the transmission of any signal across time and space (at a speed greater than the speed of light). Additionally, up to 85% of all Mass and Energy in the universe cannot be detected empirically but instead is hypothesized to comprise of "Dark Matter" and "Dark Energy", which are hypothesized to "cause" the accelerated expansion of the physical universe.